More of me: self-prioritization of numeric stimuli - Keil, J; Barutchu, A; Desebrock, C; Spence, C (American Psychological Association, 2023)
People process stimuli that have been arbitrarily associated with the self versus with a stranger preferentially, but congruence effects can modulate self-prioritization, as when the self is paired with, for example, symmetrical versus asymmetrical stimuli. In two experiments, we examined the interaction of self-prioritization with number magnitude when participants associated the self or a stranger with specific number symbols such as ‘2’ presented as natural, negative and ordinal number types (Exp. 1), or abstract numeric concepts, such as ‘larger than 5’ (Exp. 2). Empathy and personal distance were also assessed. While self-prioritization emerged in both experiments, number type (natural, ordinal, and negative) had no effect on performance. Furthermore, correlations with empathy and personal distance did not emerge consistently. An interaction between number magnitude and selfassignment was observed for the magnitude comparison matching task (e.g., >5) (Exp 2), but not in the specific number (e.g. “8”) matching task (Exp 1). The null interaction may reflect the fact that encoding symbol identity, but not number magnitude, was sufficient for the symbol matching task. The order of number and self-associations also had an effect. In sum, this study is the first to show that self-prioritization emerges for symbolic numbers and can even occur with abstract categories, such as a range of numbers (e.g. >5). Furthermore, congruence effects between number concepts and labels (e.g. for the stranger, less is better) may also affect performance. However, this would appear to depend on the task context, such as whether numeric magnitude was needed to complete the task.